Synthesis and Biological Evaluation of Metronidazole Derivatives as Anti-Giardia Agents - Bahador shahriari; Zahra Rezaei; Soghra Khabnadideh; Hossein Sadeghpour; Gholam Reza Hatam; Qasem Asgari; Amin Kiani; Fardad Firoozi (Shiraz University of Medical Sciences, 2015)
Nitroimidazole derivatives such as Metronidazole (MTZ) have been used as anti- protozoa and anti-anaerobic bacteria. In this study several compounds of MTZ derivatives were synthesized and evaluated against Giardia lamblia cyst. Firs MTZ were reacted with several alkyl halide to obtain O-alkyl MTZ derivatives, then products were purified and their chemical structures were confirmed by elemental and spectral analysis (1HNMR and Mass). In order to biological      evaluation all compounds were investigated against 25 Giardia samples isolated from giarfdiasis patients. Results showed compound 2a had the most activity on cyst of Giardia in comparison with MTZ.